Case Report: A case of Felty’s syndrome with initial presentation of pleural effusion and subsequent Escherichia coli pyothorax - Yang, Haifeng; Wang, Weiqin; Liu, Yongfeng; Yang, Yibo; Su, Yiliang (Frontiers in Pharmacology, 2025)
BackgroundPleural effusion is a common disease in respiratory medicine, and rheumatoid arthritis (RA) is one of the causes of pleural effusion. Felty’s syndrome is a special manifestation of RA. We report a case of Felty’s syndrome with pleural effusion as the initial symptom and the subsequent diagnosis and treatment of the patient’s secondary pyothorax.Case presentationWe report the case of a 78-year-old male who was admitted to the hospital after more than 1 year of discovered pleural effusion. After consultation with the Department of Rheumatology and Immunology, and considering the patient’s symptoms of joint deformity and swelling pain, combined with decreased white blood cells, decreased platelets, and splenomegaly, the patient was diagnosed with RA Felty’s syndrome. The patient was treated with iguratimod and methylprednisolone. Three months later, the patient was diagnosed as Escherichia coli empyema. The patient was treated with intravenous and sensitive anti-infection therapy combined with medical thoracoscopy, achieving good therapeutic effects.ConclusionFelty’s syndrome is a rare manifestation of RA. Pleural effusion may be the initial manifestation of RA, and secondary infections are prone to occur during the treatment of RA and Felty’s syndrome. The combination of sensitive antibiotics and medical thoracoscopy can effectively treat secondary pyothorax.